Allogeneic CD20‐targeted γδ T cells exhibit innate and adaptive antitumor activities in preclinical B‐cell lymphoma models. Issue 2 (2nd February 2022) - Nishimoto, Kevin P; Barca, Taylor; Azameera, Aruna; Makkouk, Amani; Romero, Jason M; Bai, Lu; Brodey, Mary M; Kennedy‐Wilde, Jackie; Shao, Hui; Papaioannou, Stephanie; Doan, Amy; Masri, Cynthia; et al.
Abstract: Objectives: Autologous chimeric antigen receptor (CAR) αβ T‐cell therapies have demonstrated remarkable antitumor efficacy in patients with haematological malignancies; however, not all eligible cancer patients receive clinical benefit. Emerging strategies to improve patient access and clinical responses include using premanufactured products from healthy donors and alternative cytotoxic effectors possessing intrinsic tumoricidal activity as sources of CAR cell therapies. γδ T cells, which combine innate and adaptive mechanisms to recognise and kill malignant cells, are an attractive candidate platform for allogeneic CAR T‐cell therapy. Here, we evaluated the manufacturability and functionality of allogeneic peripheral blood‐derived CAR + Vδ1 γδ T cells expressing a second‐generation CAR targeting the B‐cell‐restricted CD20 antigen. Methods: Donor‐derived Vδ1 γδ T cells from peripheral blood were ex vivo ‐activated, expanded and engineered to express a novel anti‐CD20 CAR. In vitro and in vivo assays were used to evaluate CAR‐dependent and CAR‐independent antitumor activities of CD20 CAR + Vδ1 γδ T cells against B‐cell tumors. Results: Anti‐CD20 CAR + Vδ1 γδ T cells exhibited innate and adaptive antitumor activities, such as in vitro tumor cell killing and proinflammatory cytokine production, in addition to in vivo tumor growth inhibition of B‐cell lymphoma xenografts in immunodeficient mice. Furthermore, CD20 CAR + Vδ1 γδ T cells did not induce xenogeneic graft‐versus‐host disease in immunodeficient mice. Conclusion: These preclinical data support the clinical evaluation of ADI‐001, an allogeneic CD20 CAR + Vδ1 γδ T cell, and a phase 1 study has been initiated in patients with B‐cell malignancies (NCT04735471). Abstract : The findings of our study demonstrate preclinical proof of concept for a CD20 CAR + Vδ1 γδ T‐cell product, manufactured at clinical scale, in the treatment of CD20 + B‐cell malignancies. Complemented by innate and adaptive antitumor immunity, CD20 CAR + Vδ1 γδ T cells have a unique advantage as an allogeneic CAR T‐cell product platform and, as a consequence, have the potential to improve clinical responses in eligible cancer patients. A phase 1 clinical study evaluating ADI‐001, an allogeneic CD20 CAR + Vδ1 γδ T‐cell product, in relapsed/refractory B‐cell NHL patients has been initiated (NCT04735471).